Correction: Mucosal fluid glycoprotein DMBT1 suppresses twitching motility and virulence of the opportunistic pathogen Pseudomonas aeruginosa. - Jianfang Li; Matteo M E Metruccio; Benjamin E Smith; David J Evans; Suzanne M J Fleiszig (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1006392.].